THE INFLUENCE OF SURVEY, QUESTION, READ, RECITE AND REVIEW (SQ3R) METHOD AND READING INTEREST TOWARDS READING COMPREHENSION OF THE NINTH GRADE STUDENTS OF SMP N 13 OF PALEMBANG - Vera Afriani (ELTE Journal (English Languange Teaching and Education), 2019)
AbstractThis research investigates the influence of Survey, Question, Read, Recite and Review (SQ3R) method and reading interest towards reading comprehension of the ninth grade students of SMP N 13 of Palembang. The aim of this study was to find out whether or not there was a significant difference in reading comprehension after the students with high and low level of reading interest being taught by using SQ3R method, and to find out the significant interaction effects of the method and the reading interest towards the students reading comprehension. In this study, 80 students of the ninth grade of SMP N 13 of Palembang in the academic year of 2017/2018 were chosen as sample by two stage random sampling. This study applied factorial research design. The data collecting used test and questionnaire. The data were analyzed by using Paired Sample t-test, Independent Sample t-test and Two Way Anova. The results showed that, first, there was a significant difference in reading comprehension between the students who have high reading interest and those who have low reading interest taught using SQ3R method. Second, there was not any significant difference in reading comprehension between the students who have high reading interest and those who have low reading interest taught by traditional teaching method. Third, there was a significant difference in reading comprehension between the students who have high reading interest and those who have low reading interest taught using SQ3R method and traditional teaching method. At last, there were not any significant interaction effects of SQ3R method and reading interest towards the students’ reading comprehension. It can be concluded that the SQ3R method is effective and applicable to all levels of students' reading interest.Keywords: SQ3R Method, Traditional Teaching Mehod, Reading Interest, Reading Comprehension.